Sclerotic composition and two-component sclerotic composition
Patent Information
- Application Number
- JP2022578727
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-17
- Filing Date
- 2021-09-28
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-09-28
AI Technical Summary
【0103】 本発明では、製造工程が簡単で且つ製造費用が節減され、長期保管安定性が確保される硬化性組成物を提供することができる。
Smart Images

Figure 0007640171000018 
Figure 0007640171000001 
Figure 0007640171000002
Abstract
Description
[Technical field]
[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0127591 filed on September 29, 2020, and Korean Patent Application No. 10-2021-0124663 filed on September 17, 2021, and all contents disclosed in the documents of the Korean Patent Application are incorporated as part of this specification.
[0002] Technical Field The present invention relates to a curable composition and a two-part curable composition. [Background technology]
[0003] Heat dissipation materials are used in a variety of fields. For example, in the case of vehicles, heat dissipation materials can be used to dispose of heat generated from battery modules and on-board chargers (OBCs) that charge batteries built into rechargeable electric vehicles, and heat dissipation materials can also be used in components that consume high power and generate a lot of heat, such as LED modules, to extend the lifespan of the LED modules.
[0004] Silicone-based resin compositions have excellent heat resistance and can be used as heat dissipation materials. In order to realize excellent conductive properties, inorganic hydroxide fillers can be added to the silicone-based resin compositions.
[0005] However, when an inorganic hydroxide filler is used without surface treatment, the highly reactive inorganic hydroxide filler reacts with a curing agent in the resin composition, and the viscosity and hardness of the resin composition or the cured product deviate from the designed range over time, which may cause a problem of reduced long-term storage stability.
[0006] To solve these problems, there is a method of surface-treating an inorganic hydroxide filler and then mixing it with a silicone-based resin composition. However, this method requires a lot of time and cost, so a method is needed that can ensure long-term storage stability of the resin composition even without surface treatment of the filler. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a curable composition having excellent storage stability since no change in physical properties such as viscosity or hardness occurs during storage, and a two-part type curable composition containing such a curable composition.
[0008] Another object of the present invention is to provide a curable composition having excellent storage stability without using a separate additive or without a surface treatment process of a thermally conductive filler, and a two-part curable composition including such a curable composition. [Means for solving the problem]
[0009] Of the physical properties referred to in this specification, those properties that are affected by the measurement temperature are those measured at room temperature, unless otherwise specified.
[0010] The term "room temperature" as used herein means a natural temperature without heating or cooling, for example, any one of temperatures within a range of about 10° C. to 30° C., for example, about 15° C., about 18° C., about 20° C., about 23° C., or about 25° C. In addition, unless otherwise specified in the present specification, the unit of temperature is ° C.
[0011] As used herein, unless otherwise specified, the term "alkenyl group" can mean a straight-chain, branched-chain, or cyclic alkenyl group having 2 to 20 carbon atoms, 2 to 16 carbon atoms, 2 to 12 carbon atoms, 2 to 8 carbon atoms, or 2 to 4 carbon atoms.
[0012] In this specification, unless otherwise specified, the term "alkyl group or alkoxy group" can mean a linear, branched, or cyclic alkyl group or alkoxy group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms.
[0013] The term "aryl group" as used herein, unless otherwise specified, may refer to a compound containing a benzene structure, a compound containing a structure in which two or more benzenes are linked by a linker, or a compound containing a structure in which two benzenes are condensed or bonded while sharing one or two carbon atoms, or a monovalent residue derived from a derivative of any one of the compounds mentioned above. The scope of the aryl group as used herein may include not only functional groups commonly referred to as aryl groups, but also so-called aralkyl groups or arylalkyl groups. The aryl group may be, for example, an aryl group having 6 to 25 carbon atoms, 6 to 21 carbon atoms, 6 to 18 carbon atoms, or 6 to 12 carbon atoms. Examples of the aryl group include a phenyl group, a dichlorophenyl group, a chlorophenyl group, a phenylethyl group, a phenylpropyl group, a benzyl group, a tolyl group, a xylyl group, and a naphthyl group.
[0014] The alkenyl group, alkoxy group, alkyl group, or aryl group may be optionally substituted with one or more substituents, examples of which include, but are not limited to, halogens such as chlorine or fluorine, epoxy groups such as glycidyl groups, epoxyalkyl groups, glycidoxyalkyl groups, or alicyclic epoxy groups, acryloyl groups, methacryloyl groups, isocyanate groups, thiol groups, and monovalent hydrocarbon groups.
[0015] As used herein, the term "M unit" generally refers to a 3 SiO 1 / 2 ), and the term “D unit” generally refers to the so-called monofunctional siloxane unit, which may be represented by (R 2 SiO 2 / 2), and the term "T unit" generally refers to a so-called difunctional siloxane unit, which may be represented by (RSiO 3 / 2 ), and the term "Q unit" generally refers to a so-called trifunctional siloxane unit, which may be represented by (SiO 4 / 2 In the formula of each siloxane unit, R is a functional group bonded to silicon (Si), and may be, for example, hydrogen, an alkyl group, an alkenyl group, an aryl group, an alkoxy group, or an epoxy group.
[0016] The curable composition of the present invention can include an alkenyl group-containing polyorganosiloxane component, a silicon-bonded hydrogen-containing polyorganosiloxane component, and a filler component having a filler having a hydroxyl group on the surface. The curable composition of the present invention is cured by a reaction (addition reaction (hydrosilylation reaction product)) between the alkenyl group of the alkenyl group-containing polyorganosiloxane component and the hydrogen of the silicon-bonded hydrogen-containing polyorganosiloxane component.
[0017] The curable composition may be, for example, a one-component resin composition, a base composition of a two-component resin composition, a curing agent composition of a two-component resin composition, or a mixture of a base composition and a curing agent composition of a two-component resin composition. The one-component resin composition is a resin composition in which the curable components are mixed and stored, and the two-component resin composition is a resin composition in which the curable components are physically separated into a base composition and a curing agent composition and stored. In the case of a two-component resin composition, the base composition and the curing agent composition are mixed under conditions that allow curing to occur at the time of use.
[0018] As used herein, the term "polyorganosiloxane component" may refer to a mixture of polyorganosiloxanes and / or a mixture of polyorganosiloxanes and siloxane monomers. In more specific examples, the polyorganosiloxane component may be the result of a polymerization reaction carried out to obtain a specific target polyorganosiloxane, or a mixture of the results of two or more of such polymerization reactions.
[0019] The alkenyl group-containing polyorganosiloxane component in the curable composition may be any known polyorganosiloxane component without any particular limitation. In one example, the polyorganosiloxane component may be a polyorganosiloxane component containing a linear polyorganosiloxane.
[0020] As is well known, linear polyorganosiloxane is a polyorganosiloxane having a structure in which both ends of a chain structure consisting of D units are blocked with M units.
[0021] The linear polyorganosiloxane is a polyorganosiloxane having a structure in which both ends of a chain structure consisting of D units are blocked with M units.
[0022] In the above structure, various types of units can be used as the D unit. For example, the D unit may be a so-called dialkylsiloxane unit (R 2 SiO 2 / 2 Difunctional siloxane units in which all R are alkyl groups), diaryl siloxane units (R 2 SiO 2 / 2 Difunctional siloxane units in which all R are aryl groups), dialkenyl siloxane units (R 2 SiO 2 / 2 Bifunctional siloxane units in which all R are alkenyl groups), alkylaryl siloxane units (R 2 SiO 2 / 2 Bifunctional siloxane units in which one R is an alkyl group and the other R is an aryl group), alkylalkenylsiloxane units (R 2 SiO 2 / 2 Bifunctional siloxane units in which one R is an alkyl group and the other R is an alkenyl group) and arylalkenylsiloxane units (R 2 SiO 2 / 2 At least one unit selected from the group consisting of difunctional siloxane units in which one R is an alkenyl group and the other R is an aryl group may be applied.
[0023] Suitable D units include the dialkylsiloxane unit (R 2 SiO 2 / 2 Bifunctional siloxane units in which all R are alkyl groups) and / or alkylalkenyl siloxane units (R 2 SiO 2 / 2 An example is a difunctional siloxane unit in which one R is an alkyl group and the other R is an alkenyl group.
[0024] In the linear polyorganosiloxane structure, the M units at both ends of the chain structure consisting of D units are, for example, alkenyldialkylsiloxane units (R 3 SiO 1 / 2 monofunctional siloxane units in which one of the R's is an alkenyl group and the remaining two are alkyl groups) and / or trialkylsiloxane units (R 3 SiO 1 / 2 For example, in the case of a structure in which both ends are terminated with alkenyl groups, an alkenyldialkylsiloxane unit can be used as the M unit.
[0025] As one example, the polyorganosiloxane having an alkenyl group is a linear polyorganosiloxane in which the D unit in the main chain structure is a dialkylsiloxane unit (R 2 SiO 2 / 2 Bifunctional siloxane units in which all R are alkyl groups) and / or alkylalkenyl siloxane units (R 2 SiO 2 / 2 In the structure, one R is an alkyl group and the other R is an alkenyl group (bifunctional siloxane unit), and the M units at both ends are alkenyldialkylsiloxane units (R 3 SiO 1 / 2 Polyorganosiloxanes having the structure (monofunctional siloxane units in which one R is an alkenyl group and the remaining two are alkyl groups) can be used.
[0026] When two or more kinds of D units are used as the D units of the main chain, the form of the main chain may be that of a random copolymer, a block copolymer or a gradient copolymer.
[0027] As one example, the polyorganosiloxane component may be a component represented by the following average unit formula A:
[0028] The term "average unit formula" refers to a unit formula that indicates the ratio of the molar number of each siloxane unit present when the total number of moles of all siloxane units (M, D, T and Q units) present in the polyorganosiloxane component is converted to 1.
[0029] [Average Unit Formula A] (R 1 R 2 2 SiO 1 / 2 ) a (R 2 3 SiO 1 / 2 ) b (R 1 R 2 SiO 2 / 2 ) c (R 2 2 SiO 2 / 2 ) d
[0030] Average unit formula A, R 1 is an alkenyl group, R 2 is an alkyl group or an aryl group, a+b+c+d is 1, (a+b) is a number in the range of 0.001 to 0.05, (c+d) is a number in the range of 0.7 to 0.999, and b / a and c / d are each independently a number in the range of 0 to 10.
[0031] In the average unit formula A, (a+b) may be, for example, 0.007 or more, or 0.009 or more, or about 0.045 or less, 0.04 or less, 0.035 or less, 0.03 or less, 0.025 or less, 0.02 or less, or 0.015 or less.
[0032] In the average unit formula A, (c+d) may be, in other examples, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, or 0.95 or more, or 0.997 or less, 0.995 or less, 0.993 or less, or 0.991 or less.
[0033] In the average unit formula A, b / a may be, for example, about 0 to 9, 0 to 8, 0 to 7, 0 to 6, 0 to 5, 0 to 4, 0 to 3, 0 to 2, 0 to 1, or 0 to 0.5, or may be 0.
[0034] In the average unit formula A, c / d may be, for example, about 0 to 9, 0 to 8, 0 to 7, 0 to 6, 0 to 5, 0 to 4, 0 to 3, 0 to 2, 0 to 1, or 0 to 0.5, or may be 0.
[0035] In one embodiment, the alkenyl group-containing polyorganosiloxane component may include a polyorganosiloxane represented by the following Formula 1:
[0036] [ka]
[0037] In formula 1, R 5 is an alkenyl group, R 6 is an alkyl group or an aryl group, and n is a number within the range of 30 to 300. In Chemical Formula 1, n may be, for example, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, 110 or more, 120 or more, 130 or more, 140 or more, 150 or more, 160 or more, 170 or more, 180 or more, 190 or more, 200 or more, 210 or more, 220 or more, 230 or more, 240 or more, or 250 or more, or 290 or less, 280 or less, 270 or less, 260 or less, 250 or less, 240 or less, 230 or less, 220 or less, 210 or less, 200 or less, 190 or less, 180 or less, 170 or less, 160 or less, 150 or less, 140 or less, 130 or less, 120 or less, 110 or less, or 100 or less.
[0038] In the definition of Chemical Formula 1, specific types of alkenyl group, alkyl group, and aryl group are as described at the beginning of the solution of the problem of this specification.
[0039] The alkenyl group-containing polyorganosiloxane component may contain alkenyl groups at about 0.05 to 5 mmol / g. The ratio of the alkenyl groups may be, for example, about 0.1 mmol / g or more, 0.15 mmol / g or more, 0.2 mmol / g or more, 0.25 mmol / g or more, or 4 mmol / g or less, 3 mmol / g or less, 2 mmol / g or less, 1 mmol / g or less, 0.5 mmol / g or less, or 0.3 mmol / g or less. The ratio is a value calculated by the ratio of alkenyl groups in the alkenyl group-containing polyorganosiloxane component in the liquid curing agent composition excluding the filler component.
[0040] The ratio of the alkenyl groups may be varied depending on the specific application of the curable composition, and when it satisfies the specified range, it can be mixed with a filler component to ensure the desired viscosity.
[0041] For example, when the curable composition is a curing agent composition of a two-component curable composition, the ratio of the alkenyl group may be additionally about 0.1 mmol / g or more, 0.15 mmol / g or more, 0.2 mmol / g or more, 0.25 mmol / g or more, or about 4 mmol / g or less, 3 mmol / g or less, 2 mmol / g or less, 1 mmol / g or less, 0.5 mmol / g or less, or 0.3 mmol / g or less within the above range.
[0042] In another example, when the curable composition is a mixture of a base and a curing agent composition of a two-component curable composition or a one-component curable composition, the ratio of the alkenyl group may be adjusted within the above range to be 0.1 mmol / g or more, 0.15 mmol / g or more, 0.2 mmol / g or more, 0.25 mmol / g or more, 0.3 mmol / g or more, or 0.35 mmol / g or more, and / or 4.5 mmol / g or less, or 4 mmol / g or less.
[0043] The alkenyl group content and silicon-bonded hydrogen content of the polyorganosiloxane component referred to in this specification are the same as those described in the Examples below for the polyorganosiloxane component. 1 H NMR and / or 29 This is a value obtained through Si NMR analysis. This method differs from the value theoretically obtained through the chemical formula of the polyorganosiloxane contained in the polyorganosiloxane component. In other words, since various types of polyorganosiloxanes that belong to the same category of chemical formula but have different detailed structures can exist in the polyorganosiloxane component (for example, multiple polyorganosiloxanes with different n values can exist in the structure of Chemical Formula 1), this method cannot confirm the exact ratio between the curable functional groups (ratio of alkenyl groups and silicon-bonded hydrogen).
[0044] The ratio plays an important role in ensuring the desired storage stability (suppression of changes in viscosity and hardness over time) and thixotropy, etc., and this is 1 H NMR and / or 29 It must be determined based on the results of Si NMR analysis.
[0045] In one example, the polyorganosiloxane having an alkenyl group may have a number average molecular weight (Mn) in the range of 2500 g / mol to 20000 g / mol. In another example, the number average molecular weight (Mn) of the polyorganosiloxane having an alkenyl group may be 3000 g / mol or more, 3500 g / mol or more, 4000 g / mol or more, 4500 g / mol or more, 5000 g / mol or more, or 5500 g / mol or more, or 19000 g / mol or less, 18000 g / mol or less, 17000 g / mol or less, 16000 g / mol or less, 15000 g / mol or less, or 14000 g / mol or less.
[0046] The polyorganosiloxane component containing silicon-bonded hydrogen in the curable composition may be any known material without any particular limitation. For example, the polyorganosiloxane component may be a linear polyorganosiloxane, i.e., a polyorganosiloxane having a structure in which both ends of a chain structure consisting of D units are blocked by M units.
[0047] In the above structure, various types of units can be used as the D unit. For example, the D unit may be a so-called dialkylsiloxane unit (R 2 SiO 2 / 2 Difunctional siloxane units in which all R are alkyl groups), diaryl siloxane units (R 2 SiO 2 / 2 Difunctional siloxane units in which all R are aryl groups), dihydrogen siloxane units (R 2 SiO 2 / 2 Bifunctional siloxane units in which all R are hydrogen), alkylaryl siloxane units (R 2 SiO 2 / 2 (a bifunctional siloxane unit in which one R is an alkyl group and the other R is an aryl group), and (R 2 SiO 2 / 2 Bifunctional siloxane units in which one R is an alkyl group and the other R is hydrogen) and arylhydrogensiloxane units (R 2 SiO 2 / 2 At least one unit selected from the group consisting of difunctional siloxane units in which one R is hydrogen and the other R is an aryl group may be applied.
[0048] Suitable D units include the dialkylsiloxane unit (R 2 SiO 2 / 2 Difunctional siloxane units in which all R are alkyl groups) and / or alkylhydrogen siloxane units (R 2 SiO 2 / 2 An example is a difunctional siloxane unit in which one R is an alkyl group and the other R is hydrogen.
[0049] In the linear polyorganosiloxane structure, examples of the D units at both ends of the chain structure composed of D units include hydrogen dialkylsiloxane units (R 3 SiO 1 / 2 monofunctional siloxane units in which one of the R's is hydrogen and the remaining two are alkyl groups) and / or trialkylsiloxane units (R 3 SiO 1 / 2 For example, in the case of a structure in which both ends are terminated with silicon-bonded hydrogen, a hydrogen dialkyl siloxane unit can be used as the M unit.
[0050] As one example, the silicon-bonded hydrogen-containing polyorganosiloxane component may be a component represented by the following average unit formula B:
[0051] [Average unit formula B] (HR 3 2 SiO 1 / 2 ) a (R 3 3 SiO 1 / 2 ) b (R 3 2 SiO 2 / 2 ) c (HR 3 SiO 2 / 2 ) d
[0052] Average unit formula B, R 3 is an alkyl group or an aryl group, a+b+c+d is 1, a is a number in the range of 0.001 to 0.2, b is a number in the range of 0.01 to 0.8, c is a number in the range of 0.01 to 0.7, and d may be a number in the range of 0.001 to 0.4.
[0053] In other examples, the a may be a number within the range of 0.003 or more, 0.005 or more, 0.007 or more, 0.009 or more, 0.01 or more, 0.03 or more, 0.05 or more, 0.07 or more, or 0.085 or more, or within the range of 0.15 or less, or 0.1 or less.
[0054] In other examples, the b may be a number within the range of 0.05 or more, 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.35 or more, or 0.4 or more, or 0.7 or less, 0.6 or less, 0.5 or less, or 0.45 or less.
[0055] In other examples, c may be a number within the range of 0.05 or more, 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, or 0.3 or more, or may be a number within the range of 0.65 or less, 0.6 or less, 0.55 or less, 0.5 or less, 0.45 or less, 0.4 or less, or 0.35 or less.
[0056] In another embodiment, d may be in the range of 0.003 or more, 0.005 or more, 0.007 or more, 0.009 or more, 0.01 or more, 0.03 or more, 0.05 or more, 0.07 or more, 0.09 or more, 0.11 or more, or 0.13 or more, or in the range of 0.35 or less, 0.3 or less, 0.25 or less, or 0.2 or less. In one embodiment, the silicon-bonded hydrogen-containing polyorganosiloxane component may include a first polyorganosiloxane component including a polyorganosiloxane of the following formula 2 and a second polyorganosiloxane component including a polyorganosiloxane of the following formula 3:
[0057] [ka]
[0058] In formula 2, R 3is an alkyl group or an aryl group, and m is a number within the range of 4 to 25. In Chemical Formula 2, m may be, for example, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 11 or more, 12 or more, 13 or more, or 14 or more, or 23 or less, 21 or less, 19 or less, 17 or less, 15 or less, 13 or less, 11 or less, or 9 or less.
[0059] [ka]
[0060] In formula 3, R 4 is an alkyl group or an aryl group, p is a number within the range of 20 to 60, and q is a number within the range of 3 to 20. In Chemical Formula 3, p may be, in other examples, 21 or more, 22 or more, 23 or more, 24 or more, 25 or more, 26 or more, 27 or more, 28 or more, 29 or more, or 30 or more, or 55 or less, 50 or less, 45 or less, or 40 or less. In Chemical Formula 3, q may be, in other examples, 4 or more, 6 or more, 7.5 or more, 9 or more, or 11 or more, or 18 or less, 17 or less, 16 or less, 15 or less, or 14 or less.
[0061] In the above Chemical Formula 2 or Chemical Formula 3, the specific types of the alkyl group and the aryl group are as described at the beginning of the solution of the problem of this specification.
[0062] The first polyorganosiloxane component may have a molar content of silicon-bonded hydrogen of 0.5 to 10 mmol / g. In other examples, the first polyorganosiloxane component may contain silicon-bonded hydrogen at 1.2 mmol / g or more, 1.4 mmol / g or more, 1.6 mmol / g or more, 1.8 mmol / g or more, 2 mmol / g or more, 2.2 mmol / g or more, 2.4 mmol / g or more, or 2.6 mmol / g or more, or at 9 mmol / g or less, 8 mmol / g or less, 7 mmol / g or less, 6 mmol / g or less, 5 mmol / g or less, or 4 mmol / g or less.
[0063] The second polyorganosiloxane component may have a molar content of silicon-bonded hydrogen of 0.5 to 6 mmol / g. In another example, the second polyorganosiloxane component may have a silicon-bonded hydrogen content of 1 mmol / g or more, 2 mmol / g or more, 3 mmol / g or more, or 4 mmol / g or more, or 5.5 mmol / g or less, 5 mmol / g or less, or 4.5 mmol / g or less.
[0064] In one example, when the silicon-bonded hydrogen-containing polyorganosiloxane component includes both the first polyorganosiloxane component and the second polyorganosiloxane component, the ratio (H1 / H2) of the number of moles of silicon-bonded hydrogen of the second polyorganosiloxane component to the number of moles of silicon-bonded hydrogen of the first polyorganosiloxane component (H1) may be in the range of 0.5 to 10.
[0065] In other examples, the ratio (H1 / H2) may be 1 or more, 1.5 or more, 2 or more, 2.5 or more, 3 or more, 3.5 or more, or 4 or more, or may be 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, or 4.5 or less.
[0066] In the curable composition, the ratio (H / Ak) of the number of moles of silicon-bonded hydrogen (H) in the silicon-bonded hydrogen-containing polyorganosiloxane component to the number of moles of alkenyl groups (Ak) in the alkenyl group-containing polyorganosiloxane component may be adjusted within a range of 2 to 10. In other examples, the range may be adjusted to 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, 2.5 or more, 2.6 or more, 2.7 or more, or 2.8 or more, or to about 9 or less, 8 or less, or 7 or less.
[0067] The ratios may vary depending on the particular application of the curable composition.
[0068] For example, when the curable composition is a curing agent composition of a two-component curable composition, the ratio may be additionally adjusted within the above range to within a range of 3 or more, 3.5 or more, 4 or more, 4.5 or more, 5 or more, 5.5 or more, or 6 or more, and / or within a range of 9 or less, 8.5 or less, 8 or less, 7.5 or less, or 7 or less.
[0069] In another example, when the curable composition is a mixed composition of a base agent and a curing agent composition of a two-component curable composition or a one-component composition, the ratio may be adjusted within the above range to be additionally within a range of 2.2 or more, 2.4 or more, 2.6 or more, or 2.8 or more, and / or within a range of 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or 3 or less.
[0070] When a thermally conductive filler is used as a filler in the curable composition, the heat dissipation or thermal conductivity of the curable composition or its cured product can be ensured.
[0071] The thermally conductive filler is a filler that enables a curable composition to which the filler is applied to form a cured product exhibiting a thermal conductivity of about 1 W / mK or more. The thermal conductivity of the cured product may be about 1.2 W / mK or more, 1.4 W / mK or more, 1.6 W / mK or more, or 1.8 W / mK or more, or about 400 W / mK or less, about 350 W / mK or less, about 300 W / mK or less, 200 W / mK or less, 100 W / mK or less, 50 W / mK or less, 10 W / mK or less, 8 W / mK or less, 6 W / mK or less, 4 W / mK or less, or 2 W / mK or less.
[0072] The filler component of the present invention may have a filler having a hydroxyl group on the surface. In one embodiment, the filler is aluminum hydroxide (Al(OH) 3 ), magnesium hydroxide (Mg(OH) 2 ), potassium hydroxide (Ca(OH) 2 ) and hydromagnesite (Mg 5 (CO 3 ) 4 (OH) 2 4H 2O). Such fillers have excellent thermal conductivity and a low specific gravity, which is advantageous for weight reduction. The shape of the filler that can be applied is not particularly limited, and for example, spherical fillers, needle-shaped or plate-shaped fillers, or other amorphous fillers can be used.
[0073] In one example, the filler having a hydroxyl group on the surface may have an average particle size in the range of 0.001 μm to 100 μm, where the average particle size is a D50 particle size measured by the method described in the examples below. In other examples, the average particle size of the filler may be 0.005 μm or more, 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.5 μm or more, 0.8 μm or more, 1 μm or more, 5 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, or 45 μm or more, or 95 μm or less, 90 μm or less, 85 μm or less, 80 μm or less, 75 μm or less, 70 μm or less, 65 μm or less, 60 μm or less, 55 μm or less, 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, 10 μm or less, or 5 μm or less.
[0074] In order to ensure appropriate filling properties and desired properties, a mixture of two or more fillers having different average particle sizes may be used as the filler. For example, a first filler having an average particle size of 20 μm or more and a second filler having an average particle size of 10 μm or less within the above-mentioned range may be used as the filler.
[0075] In other examples, the average particle size of the first filler may be 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, or 45 μm or more, or may be 100 μm or less, 95 μm or less, 90 μm or less, 85 μm or less, 80 μm or less, 75 μm or less, 70 μm or less, 65 μm or less, 60 μm or less, or 55 μm or less.
[0076] In addition, the average particle size of the second filler may be, in other examples, 0.001 μm or more, 0.005 μm or more, 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.5 μm or more, or 0.8 μm or more, or may be approximately 10 μm or less, 8 μm or less, 6 μm or less, 4 μm or less, or 3 μm or less.
[0077] When the first and second fillers are applied simultaneously, the ratio (D1 / D2) of the average particle diameter (D1) of the first filler based on the average particle diameter (D2) of the second filler may be within a range of 2 to 200. In other examples, the ratio (D1 / D2) may be 5 or more, 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, 35 or more, 40 or more, or 45 or more, or may be about 170 or less, 150 or less, 130 or less, 110 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, or 55 or less.
[0078] When the first and second fillers are applied simultaneously, the ratio (W1 / W2) of the weight (W1) of the first filler to the weight (W2) of the second filler may be within a range of 0.5 to 10. In other examples, the ratio (W1 / W2) may be 1 or more, 1.5 or more, or 2 or more, or about 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or 3 or less.
[0079] The filler component may be contained in the range of 200 to 900 parts by weight per 100 parts by weight of the alkenyl group-containing polyorganosiloxane component of the curable composition, and may be contained in the range of 1,000 to 30,000 parts by weight per 100 parts by weight of the silicon-bonded hydrogen-containing polyorganosiloxane component of the curable composition.
[0080] When the above range is satisfied, excellent heat dissipation properties can be ensured, and at the same time, the adhesion between the metal and the curable composition can be improved, thereby ensuring long-term storage stability of the curable composition.
[0081] In one example, the filler component may be included in an amount of 50 to 75 volume % based on the total volume of the curable composition. The volume ratio may be calculated taking into consideration the mass ratio of each component included in the curing composition and their density, and components that are not included in the final cured product of the curing composition (e.g., volatile components, solvents, etc.) are not taken into consideration in the calculation.
[0082] The curable composition may contain other necessary ingredients in addition to the above ingredients.
[0083] For example, the curable composition may further include a catalyst, for example, an addition reaction catalyst. The type of catalyst is not particularly limited, but for example, a platinum-based catalyst may be used, and the platinum-based catalyst may be a known or commercially available catalyst. The content of the catalyst is not particularly limited, and may be included in a catalytic amount depending on the composition of the curable polyorganosiloxane component.
[0084] In addition to the above components, the curable composition may further contain additives, such as pigments, dyes, dispersants, thixotropic agents, and flame retardants, if necessary.
[0085] The curable composition may be a one-part composition as described above, a base or curing agent composition of a two-part composition, or a mixture of a base and curing agent composition of a two-part composition.
[0086] In the case of a mixture of a base composition and a hardener composition of a one-part type composition or a two-part type composition, the hardenable composition may contain the above-mentioned components simultaneously.
[0087] In addition, when the curable composition is a base composition of a two-liquid composition, the base composition contains the alkenyl group-containing polyorganosiloxane component as a curable polyorganosiloxane component, and can additionally contain the catalyst and filler components.
[0088] In addition, when the resin composition is a two-liquid type curing agent composition, the curing agent composition may contain the alkenyl group-containing polyorganosiloxane component and the silicon-bonded hydrogen-containing polyorganosiloxane component as the curable polyorganosiloxane component, and may additionally contain the filler component, and may not contain a catalyst. In this case, not containing a catalyst means that it is substantially not contained, and is not intentionally added, and it can be said that it is substantially not contained when it is contained at about 0.01 wt% or less, 0.001 wt% or less, 0.0001 wt% or less, or 0.00001 wt% or less relative to the total weight of the composition.
[0089] In each of the above cases, the specific types of polyorganosiloxane component, filler component, catalyst, etc. and their blending ratios are as described above.
[0090] In one example, when the resin composition is a two-part curable composition, the resin composition includes a physically separated base composition and a curing agent composition, the base composition includes an alkenyl group-containing polyorganosiloxane component and a filler component, and the curing agent composition includes an alkenyl group-containing polyorganosiloxane component, a silicon-bonded hydrogen-containing polyorganosiloxane component, and a filler component.
[0091] In such a case, the base composition may contain a catalyst, and the hardener composition may not contain a catalyst.
[0092] In one example, in the two-part curable composition, the ratio (Ak1 / Ak2) of the number of moles of alkenyl groups in the alkenyl group-containing polyorganosiloxane component of the base composition (Ak1) and the number of moles of alkenyl groups in the alkenyl group-containing polyorganosiloxane component of the curing agent composition (Ak2) may be within the range of 0.5 to 5. Specifically, the ratio (Ak1 / Ak2) may be 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.1 or more, or 1.2 or more, or about 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, or 1.5 or less.
[0093] In one example, the ratio (H / Ak) of the total number of moles of silicon-bonded hydrogen atoms (H) to the total number of moles of alkenyl groups (Ak) in the two-part curable composition may be greater than 1. Specifically, the ratio of the total number of moles of silicon-bonded hydrogen atoms to the total number of moles of alkenyl groups may be 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, 2 or more, 3 or more, 4 or more, or 5 or more. When the ratio of the number of moles of silicon-bonded hydrogen atoms to the number of moles of alkenyl groups is adjusted within the above range, there is an advantage that the two-part curable composition can be stored for a long period of time without surface treatment of the filler. Here, the ratio of the number of moles of silicon-bonded hydrogen atoms to the total number of moles of alkenyl groups in the two-part curable composition may be the ratio of the number of moles of silicon-bonded hydrogen atoms to the total number of moles of alkenyl groups in the base composition and the curing agent composition.
[0094] In the above case, the specific types of polyorganosiloxane component, filler component, catalyst, etc. and the blending ratios thereof are as described above.
[0095] In one example, the viscosity value of the two-component curable composition may be about 1,000,000 cP or less. The lower limit may be, for example, about 2,000 cP or more. In one example, the viscosity value of the two-component curable composition may be about 950,000 cP or less, 900,000 cP or less, or about 850,000 cP or less, or about 3,000 cP or more, 4,000 cP or more, or about 5,000 cP or more. When the range is satisfied, the long-term storage stability of the composition and appropriate processability can be ensured.
[0096] The two-part curable composition of the present invention can have physical properties suitable for the applications described below after curing.
[0097] In one example, the two-part curable composition may have a certain adhesive strength at room temperature after curing. Specifically, the adhesive strength to aluminum measured according to the ASTM D1002 standard is 3.8 kgf / cm. 2 Above 4.0kgf / cm2 Above, 4.2kgf / cm 2 Above 4.4kgf / cm 2 Above, 4.6kgf / cm 2 Above, 4.8kgf / cm 2 Above 5.0kgf / cm 2 Above, 5.5kgf / cm 2 Above 6.0kgf / cm 2 or more than 6.5kgf / cm 2 The upper limit of the adhesive strength is not particularly limited, and may be, for example, 10.0 kgf / cm 2 Below, 9.0kgf / cm 2 Less than or equal to 8.0kgf / cm 2 The two-part curable composition exhibiting excellent adhesion to metal as described above can be effectively used in a variety of applications where a heat dissipating material is required.
[0098] In one example, the two-part curable composition may have a predetermined hardness at room temperature after curing. In this case, it is preferable that the cured layer of the composition has an appropriate hardness. For example, if the hardness of the cured layer is too high, the cured layer may have a brittle property, which may adversely affect reliability. In consideration of this, the hardness of the cured layer may be adjusted to ensure impact resistance and vibration resistance, and thus durability of the product. For example, the hardness of the cured layer may be 50 or more, 55 or more, 60 or more, 65 or more, or 70 or more, or 90 or less, 88 or less, 86 or less, 84 or less, or 82 or less, in Shore OO type. The hardness within the above range may be adjusted by the content of the filler and the curing agent in the two-part curable composition.
[0099] In one embodiment, the two-component curable composition has a hardness (H 0 ) and hardness (H 15 ) ratio (H 0 / H 15 ) may be 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, or 0.8 or more. 0 and H 15) may be a shore OO type, and the content of the filler and the hardener in the two-part hardenable composition is the above ratio (H 0 / H 15 ) can be adjusted.
[0100] The two-part curable composition of the present invention may be applied to various applications requiring a heat dissipation material, and the scope of the applications is not particularly limited. For example, in battery-related technology, the two-part curable composition may be applied as a heat dissipation material for a battery module or a battery pack, or as a heat dissipation material for an OBC (On Board Charger) for a vehicle. Therefore, the present invention also relates to a battery module, a battery pack, or an on-board charger (OBC) including the two-part curable composition or a cured product thereof as a heat dissipation material. In the battery module, battery pack, or on-board charger, the application position or application method of the two-part curable composition or the cured product is not particularly limited, and known methods may be applied. In addition, the two-part curable composition of the present invention is not limited to the above applications, and may be effectively applied to various applications requiring excellent heat dissipation properties, storage stability, and adhesive strength.
[0101] In another embodiment of the present invention, the present invention may relate to electronic equipment or devices having a cured product of the two-part curable composition. The type of electronic equipment or devices is not particularly limited, and examples thereof include audio video navigation (AVN) for vehicles, on-board charger (OBC) modules for electric vehicles, LED modules, or IC chips, and computers and mobile devices including the same.
[0102] The cured product of the two-part curable composition can dissipate heat within the equipment or device and can provide resistance to impact and insulation properties. Effect of the Invention
[0103] The present invention can provide a curable composition which can be produced by a simple process, reduces production costs, and ensures long-term storage stability. [Brief description of the drawings]
[0104] [Figure 1] FIG. 1 is a graph showing the change in hardness over storage time for the cured products of the curable compositions of Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0105] The present invention will now be described in detail with reference to the following examples, but the scope of the present invention is not limited to the following examples.
[0106] 1.Hardness The base composition and the hardener composition prepared in the Examples or Comparative Examples were placed in a two-liquid cartridge, mixed in a volume ratio of 1:1, and hardened into a film having a thickness of about 5 mm. The hardness of the film surface was measured according to the ASTM D 2240 standard. An ASKER Durometer was used for the hardness measurement. A load of about 1.5 kg was applied to the flat surface of the sample to measure the initial hardness, and the hardness was evaluated by checking the stabilized measurement value after 15 seconds. Shore OO hardness was measured.
[0107] 2. Thermal Conductivity The base composition and the hardener composition prepared in the examples or comparative examples were placed in a two-liquid cartridge, mixed in a volume ratio of 1:1, and hardened into a film having a thickness of about 5 mm, and the thermal conductivity of the film in the thickness direction was measured. The thermal conductivity was measured using a hot disk measurement device according to the ISO22007-2 standard, which measures the temperature change while heating with a sensor having a double spiral structure of nickel wire.
[0108] 3.Viscosity The viscosity of the base agent, curing agent, or resin composition was measured using a viscoelasticity measuring device (Advanced Rheometic Expansion System) (Brookfield, DV3T Rheometer, CPA-52Z spindle). The temperature conditions were room temperature (about 25°C) and the gap was 5 mm. The viscosity was measured while changing the shear rate from 0.1 / s to 10.0 / s. The viscosity described below is the value at a shear rate of 1 / s.
[0109] 4. 1 H NMR analysis For polyorganosiloxane components 1 H NMR analysis was performed in a known manner. The analysis was performed at room temperature using an NMR spectrometer including a Varian Unity Inova (500 MHz) spectrometer with a triple resonance 5 mm probe. The NMR solvent (CDCl 3 ) the polyorganosiloxane components to be analyzed were diluted to a concentration of approximately 10 mg / ml and chemical transfer was expressed in ppm.
[0110] 5. 29 Si NMR analysis For polyorganosiloxane components 29 Si NMR analysis was performed in a known manner. 29 The reference compound used in the Si NMR analysis was TMS (dilute tetramethylsilane in CDCl 3 ) was used to express the chemical shift.
[0111] 6.GPC(Gel Permeation Chromatograph) The number average molecular weight (Mn) and molecular weight distribution of the polyorganosiloxane component were measured using GPC (Gel Permeation Chromatograph). The polyorganosiloxane to be analyzed was placed in a 5 mL vial and diluted with THF (tetrahydrofuran) to a concentration of approximately 5 mg / mL. Then, both the calibration standard sample and the sample to be analyzed were filtered through a syringe filter (pore size: 0.45 μm) and then measured. The analysis program used ChemStation from Agilent technologies. The elution time of the sample was compared with the calibration curve to determine the weight average molecular weight (Mw) and the number average molecular weight (Mn) respectively, and the molecular weight distribution (PDI) was calculated as the ratio (Mw / Mn). The measurement conditions for GPC are as follows.
[0112] <GPC Measurement Conditions> Instrument: 1200 series from Agilent technologies Columns: Two PLgel mixed B columns from Polymer laboratories were used Solvent: THF (tetrahydrofuran) Column temperature: 40 °C Sample concentration: 5 mg / mL, 10 μL injection Standard sample: Polystyrene (Mp: 3900000, 723000, 316500, 52200, 31400, 7200, 3940, 485)
[0113] <Example 1> Preparation of base composition A polyorganosiloxane component (VP1000, DAMIPOLYCHEM) having a viscosity of 1000 cP and containing a polyorganosiloxane of the following chemical formula A (7.92 g), a polyorganosiloxane component (DSVP100, WSsolution) having a viscosity of 100 cP and containing a polyorganosiloxane of the following chemical formula B (1.98 g) and a platinum catalyst (1,3-divinyl-1,1,3,3-tetramethyl-disiloxane-platinum (0)-complex) were mixed with aluminum hydroxide having a D50 particle size of about 50 μm and aluminum hydroxide having a D50 particle size of about 1 μm in a weight ratio of 7:3 to 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxanes of chemical formula A and chemical formula B. The aluminum hydroxide mixed filler was included in 475 parts by weight per 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxanes of chemical formula A and chemical formula B.
[0114] The polyorganosiloxane components including the polyorganosiloxane of the formula A were measured in the manner described above. 1 H NMR analysis showed Si-Vinyl peak and Si-CH 3 Area ratio (Si-CH 3 The vinyl group content was about 0.107 mmol / g. The polyorganosiloxane component including the polyorganosiloxane of the formula B was measured by the method described above. 1 H NMR analysis showed Si-Vinyl peak and Si-CH 3 Area ratio (Si-CH 3 / Si-Vinyl) was about 93, and the vinyl group content confirmed based on this was about 0.29 mmol / g.
[0115] The polyorganosiloxane component containing the polyorganosiloxane of formula A had a number average molecular weight (Mn) of about 14,800 g / mol, a weight average molecular weight (Mw) of about 35,500 g / mol, and a molecular weight distribution (PDI=Mw / Mn) of about 2.40 as measured by GPC. The polyorganosiloxane component containing the polyorganosiloxane of formula B had a number average molecular weight (Mn) of about 7,020 g / mol, a weight average molecular weight (Mw) of about 13,700 g / mol, and a molecular weight distribution (PDI=Mw / Mn) of about 1.95 as measured by GPC.
[0116] The above ingredients were put into a paste mixer and mixed and dispersed for about 3 minutes at 600 rpm revolution and 500 rpm rotation, after which the generated heat was checked and the mixture was degassed for 4 minutes at 600 rpm revolution and 200 rpm rotation in a vacuum to prepare the base composition.
[0117] [ka]
[0118] In chemical formula A, m is a number around 250.
[0119] [ka]
[0120] In chemical formula B, n is a number such as 91.
[0121] Preparation of the hardener composition 6.12g of the polyorganosiloxane component containing the polyorganosiloxane of the chemical formula A, 1.53g of the polyorganosiloxane component containing the polyorganosiloxane of the chemical formula B, 0.35g of the polyorganosiloxane component containing the polyorganosiloxane of the following chemical formula C (XL11, AB Specialty Silicones), and 10g of the curing agent part containing 2g of the polyorganosiloxane component containing the polyorganosiloxane of the following chemical formula D (CE4, AB Specialty Silicones) were mixed with aluminum hydroxide having a D50 particle size of about 50 μm and aluminum hydroxide having a D50 particle size of about 1 μm in a weight ratio of 7:3. The aluminum hydroxide mixed filler was contained in an amount of 614 parts by weight per 100 parts by weight of the polyorganosiloxane component containing polyorganosiloxanes of chemical formula A and chemical formula B, and was contained in an amount of 2000 parts by weight per 100 parts by weight of the polyorganosiloxane component containing polyorganosiloxanes of chemical formula C and chemical formula D.
[0122] The above-mentioned test was performed on a polyorganosiloxane component containing a polyorganosiloxane of formula C. 29 The results of Si NMR analysis showed that the structure of the compound with formula C has M units at both ends ((CH 3 ) 3 SiO 1 / 2 The molar ratio of hydrogen-free D units ((CH 3 ) 2 SiO 2 / 2 The molar ratio of hydrogen-containing D units (H(CH 3 )SiO 2 / 2 The molar ratio of (unit) was about 26.9 mol%. 1 Si-H peak and Si-CH peak confirmed by H NMR analysis 3 Peak ratio (Si-CH 3 / Si-H) was about 19.2, and the content of silicon-bonded hydrogen confirmed through this was about 4.14 mmol / g.
[0123] In addition, a polyorganosiloxane component containing the polyorganosiloxane of chemical formula D was 1Si-H peak and Si-CH peak confirmed by H NMR analysis 3 Peak ratio (Si-CH 3 / Si-H) was about 34.2, and the content of silicon-bonded hydrogen confirmed through this was about 2.9 mmol / g.
[0124] The components were put into a paste mixer, mixed and dispersed for about 3 minutes at 600 rpm revolution and 500 rpm rotation, and the generated heat was checked. The components were degassed for 4 minutes at 600 rpm revolution and 200 rpm rotation in a vacuum to prepare a curing agent composition.
[0125] [ka]
[0126] In chemical formula C, p is a number of about 32 and q is a number of about 13.
[0127] [ka]
[0128] In chemical formula D, n is a number such as 9.
[0129] The base composition and the hardener composition each contained 65% by volume of aluminum hydroxide, and the base composition and the hardener composition were mixed so that the molar ratio (B / A) of the alkenyl group (A) of the base composition and the hardener composition to the silicon-bonded hydrogen (B) of the hardener composition was 2.88 to produce a hardenable composition.
[0130] <Example 2> Preparation of base composition The base composition prepared in Example 1 was used.
[0131] Preparation of the hardener composition The curing agent composition was prepared in the same manner as in Example 1, except that the curing agent part was prepared containing 6.52 g of the polyorganosiloxane component containing the polyorganosiloxane of the formula A, 1.63 g of the polyorganosiloxane component containing the polyorganosiloxane of the formula B, 0.35 g of the polyorganosiloxane component containing the polyorganosiloxane of the formula C (XL11, AB Specialty Silicones), and 1.5 g of the polyorganosiloxane component containing the polyorganosiloxane of the formula D (CE4, AB Specialty Silicones).
[0132] The base composition and the hardener composition each contained 65% by volume of aluminum hydroxide, and the base composition and the hardener composition were mixed so that the molar ratio (B / A) of the alkenyl group (A) of the base composition and the hardener composition to the silicon-bonded hydrogen (B) of the hardener composition was 1.72 to produce a hardenable composition.
[0133] <Example 3> Preparation of base composition In Example 1, 9.98 g of the polyorganosiloxane component (VP1000, DAMIPOLYCHEM) containing the polyorganosiloxane of formula A used in preparing the base composition and 0.02 g of platinum catalyst (1,3-divinyl-1,1,3,3-tetramethyl-disiloxane-platinum(0)-complex) were mixed with aluminum hydroxide having a D50 particle size of about 50 μm and aluminum hydroxide having a D50 particle size of about 1 μm in a weight ratio of 7:3 to 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxane of formula A and formula B. The aluminum hydroxide mixed filler was included in an amount of 301 parts by weight per 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxane of formula A and formula B.
[0134] Preparation of the hardener composition 5g of the polyorganosiloxane component containing the polyorganosiloxane of formula A used in preparing the base composition in Example 1, 1.67g of the polyorganosiloxane component containing the polyorganosiloxane of formula C (XL11, AB Specialty Silicones), and 3.33g of the polyorganosiloxane component containing the polyorganosiloxane of formula D (CE4, AB Specialty Silicones) were mixed with 10g of the hardener part containing aluminum hydroxide having a D50 particle size of about 50 μm and aluminum hydroxide having a D50 particle size of about 1 μm in a weight ratio of 7:3. The aluminum hydroxide mixed filler was included in 600 parts by weight per 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxanes of formulas C and D.
[0135] The components were put into a paste mixer, mixed and dispersed for about 3 minutes at 600 rpm revolution and 500 rpm rotation, and the generated heat was checked. The components were degassed for 4 minutes at 600 rpm revolution and 200 rpm rotation in a vacuum to prepare a curing agent composition.
[0136] The base composition and the hardener composition each contained 54 volume % aluminum hydroxide, and the base composition and the hardener composition were mixed so that the molar ratio (B / A) of the alkenyl group (A) of the base composition and the hardener composition to the silicon-bonded hydrogen (B) of the hardener composition was 3.81 to produce a hardenable composition.
[0137] <Comparative Example 1> Preparation of base composition A polyorganosiloxane component (VP1000, DAMIPOLYCHEM) having a viscosity of 1000 cP and containing a polyorganosiloxane of the following chemical formula A (8.18 g), a polyorganosiloxane component (DSVP100, WSsolution) having a viscosity of 100 cP and containing a polyorganosiloxane of the following chemical formula B (1.67 g), and a platinum catalyst (1,3-divinyl-1,1,3,3-tetramethyl-disiloxane-platinum (0)-complex) were mixed with aluminum hydroxide having a D50 particle size of about 50 μm and aluminum hydroxide having a D50 particle size of about 1 μm in a weight ratio of 7:3 to 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxanes of chemical formula A and chemical formula B. The aluminum hydroxide mixed filler was included in 477 parts by weight per 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxanes of chemical formula A and chemical formula B.
[0138] The above ingredients were put into a paste mixer and mixed and dispersed for about 3 minutes at 600 rpm revolution and 500 rpm rotation, after which the generated heat was checked and the mixture was degassed for 4 minutes at 600 rpm revolution and 200 rpm rotation in a vacuum to prepare the base composition.
[0139] [ka]
[0140] In chemical formula A, m is a number around 250.
[0141] [ka]
[0142] In chemical formula B, n is a number such as 91.
[0143] Preparation of the hardener composition 7.96g of the polyorganosiloxane component containing the polyorganosiloxane of the chemical formula A and 1.67g of the polyorganosiloxane component containing the polyorganosiloxane of the chemical formula B were mixed with 10g of a curing agent part containing 0.37g of a polyorganosiloxane component containing the polyorganosiloxane of the following chemical formula C (FD5020, DAMIPOLYCHEM) to obtain a weight ratio of 7:3. The aluminum hydroxide mixed filler was contained in 488 parts by weight per 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxane of the chemical formula A and the chemical formula B, and was contained in 12,703 parts by weight per 100 parts by weight of the polyorganosiloxane component containing the polyorganosiloxane of the chemical formula C.
[0144] The components were put into a paste mixer, mixed and dispersed for about 3 minutes at 600 rpm revolution and 500 rpm rotation, and the generated heat was checked. The components were degassed for 4 minutes at 600 rpm revolution and 200 rpm rotation in a vacuum to prepare a curing agent composition.
[0145] [ka]
[0146] In chemical formula C, p is a number of about 39 and q is a number of about 8.
[0147] The base composition and the hardener composition each contained 65% by volume of aluminum hydroxide, and the molar ratio (B / A) of the alkenyl group (A) of the base composition and the hardener composition to the silicon-bonded hydrogen (B) of the hardener composition was 0.4 to prepare a hardenable composition.
[0148] To evaluate storage stability, the thermal conductivity and hardness of the curable composition of Comparative Example 1 were evaluated immediately after production (0 d), after 3 days (3 d), after 9 days (9 d), and after 15 days (15 d), and the results are summarized in Table 1. In addition, the thermal conductivity and hardness of the curable compositions of Examples 1 to 3 immediately after production and after the passage of time are summarized in Table 1.
[0149] [Table 1]
[0150] Referring to FIG. 1 and Table 1, the hardness of the curable composition of Comparative Example 1 decreased by 20 or more within 10 days after preparation, but the curable compositions of Examples 1 to 3 showed appropriate thermal conductivity, and therefore it was confirmed that the degree of decrease in hardness over time was small and storage stability was ensured.
Claims
1. A two-part curable composition comprising a base composition and a curing agent composition, The base composition includes an alkenyl group-containing polyorganosiloxane component and a filler component including a filler having a hydroxyl group on its surface, The curing agent composition includes an alkenyl group-containing polyorganosiloxane component, a silicon-bonded hydrogen-containing polyorganosiloxane component, and a filler component having a filler having a hydroxyl group on the surface, the volume ratio of the filler component is 54 to 65% by volume, the alkenyl group content of the alkenyl group-containing polyorganosiloxane component is within the range of 0.05 to 5 mmol / g, the ratio (H / Ak) of the number of moles of silicon-bonded hydrogen contained in the silicon-bonded hydrogen-containing polyorganosiloxane component to the number of moles of alkenyl groups contained in the alkenyl group-containing polyorganosiloxane component of the main composition and the curing agent composition is 1.7 to 3.81, The filler is aluminum hydroxide (Al(OH) 3 ), magnesium hydroxide (Mg(OH) 2 ), calcium hydroxide (Ca(OH) 2 ) and hydromagnesite (Mg 5 (CO 3 ) 4 (OH) 2 4H 2 O) one or more selected from the group consisting of The alkenyl group-containing polyorganosiloxane component of the curing agent composition has a polyorganosiloxane represented by the following formula 1: 【Chemistry 1】 In Formula 1, R 5 is an alkenyl group, R 6 is an alkyl group, n is a number in the range of 30 to 300, The silicon-bonded hydrogen-containing polyorganosiloxane component of the curing agent composition is a first polyorganosiloxane component having a compound of formula 2: a second polyorganosiloxane component having a compound of formula 3; 【Chemistry 2】 In formula 2, R 3 is an alkyl group and m is a number ranging from 7 to 25: 【Chemistry 3】 In formula 3, R 4 is an alkyl group, p is a number in the range of 20 to 60, and q is a number in the range of 3 to 20; The first polyorganosiloxane component of the curing agent composition has a silicon-bonded hydrogen content in the range of 0.5 to 10 mmol / g, and the second polyorganosiloxane component has a silicon-bonded hydrogen content in the range of 0.5 to 6 mmol / g. A two-part curable composition.
2. The ratio (Ak1 / Ak2) of the mole number (Ak1) of the alkenyl group of the alkenyl group-containing polyorganosiloxane component of the base composition and the mole number (Ak2) of the alkenyl group of the alkenyl group-containing polyorganosiloxane component of the curing agent composition is in the range of 0.5 to 5. The two-part curable composition according to claim 1, characterized in that the ratio (Ak1 / Ak2) is in the range of 0.5 to 5.
3. The two-part curable composition according to claim 1 or 2, wherein the base composition further comprises a catalyst.
4. The ratio (H1 / H2) of the number of moles of silicon-bonded hydrogen (H2) of the second polyorganosiloxane component to the number of moles of silicon-bonded hydrogen (H1) of the first polyorganosiloxane component is within the range of 0.5 to 10. The two-part curable composition according to any one of claims 1 to 3, characterized in that the ratio (H1 / H2) of the number of moles of silicon-bonded hydrogen of the second polyorganosiloxane component to the number of moles of silicon-bonded hydrogen of the first polyorganosiloxane component is within the range of 0.5 to 10.
5. The two-part curable composition according to claim 1, wherein the filler component of the curing agent composition comprises a first inorganic hydroxide having an average particle size of 20 μm or more and a second inorganic hydroxide having an average particle size of 10 μm or less.
6. The two-component curable composition according to claim 5, wherein a ratio (D1 / D2) of an average particle diameter (D1) of the first inorganic hydroxide to an average particle diameter (D2) of the second inorganic hydroxide is within a range of 2 to 200.
7. The two-component curable composition according to claim 5 or 6, wherein a ratio (W1 / W2) of a weight (W1) of the first inorganic hydroxide to a weight (W2) of the second inorganic hydroxide is within a range of 0.5 to 10.
8. The ratio of the filler component of the curing agent composition is in the range of 300 to 900 parts by weight per 100 parts by weight of the alkenyl group-containing polyorganosiloxane component in the curing agent composition. The two-part curable composition according to any one of claims 1 to 7.
9. The two-part curable composition according to any one of claims 1 to 8, characterized in that the ratio of the filler component of the curing agent composition is in the range of 1,000 to 30,000 parts by weight per 100 parts by weight of the silicon-bonded hydrogen-containing polyorganosiloxane component in the curing agent composition.
10. The two-part curable composition according to claim 1 , wherein the curing agent composition does not contain a catalyst.
11. alkenyl group-containing polyorganosiloxane component; a silicon-bonded hydrogen-containing polyorganosiloxane component; and A filler component having a filler having a hydroxyl group on a surface thereof, The volume fraction of the filler component is 54 to 65 volume %, The alkenyl group content of the alkenyl group-containing polyorganosiloxane component is within the range of 0.05 to 5 mmol / g; The ratio (H / Ak) of the moles of silicon-bonded hydrogen contained in the silicon-bonded hydrogen-containing polyorganosiloxane component to the moles of alkenyl groups contained in the alkenyl group-containing polyorganosiloxane component (Ak) is 1.7 to 3.81, The filler is aluminum hydroxide (Al(OH) 3 ), magnesium hydroxide (Mg(OH) 2 ), calcium hydroxide (Ca(OH) 2 ) and hydromagnesite (Mg 5 (CO 3 ) 4 (OH) 2 4H 2 O) one or more selected from the group consisting of The alkenyl group-containing polyorganosiloxane component has a polyorganosiloxane represented by the following chemical formula 1: 【Chemistry 4】 In Formula 1, R 5 is an alkenyl group, R 6 is an alkyl group, n is a number in the range of 30 to 300, The silicon-bonded hydrogen-containing polyorganosiloxane component is a first polyorganosiloxane component having a compound of formula 2: a second polyorganosiloxane component having a compound of formula 3; 【Chemistry 5】 In formula 2, R 3 is an alkyl group and m is a number ranging from 7 to 25: 【Chemistry 6】 In formula 3, R 4 is an alkyl group, p is a number in the range of 20 to 60, and q is a number in the range of 3 to 20; The first polyorganosiloxane component has a silicon-bonded hydrogen content in the range of 0.5 to 10 mmol / g, and the second polyorganosiloxane component has a silicon-bonded hydrogen content in the range of 0.5 to 6 mmol / g. A curable composition.
12. The ratio (H1 / H2) of the number of moles of silicon-bonded hydrogen of the second polyorganosiloxane component to the number of moles of silicon-bonded hydrogen of the first polyorganosiloxane component (H1) is within the range of 0.5 to 10. The curable composition according to claim 11, characterized in that the ratio (H1 / H2) is within the range of 0.5 to 10.
13. The curable composition according to claim 11, wherein the filler component comprises a first inorganic hydroxide having an average particle size of 20 μm or more and a second inorganic hydroxide having an average particle size of 10 μm or less.
14. The curable composition according to claim 13, characterized in that the ratio (D1 / D2) of the average particle diameter (D1) of the first inorganic hydroxide to the average particle diameter (D2) of the second inorganic hydroxide is within the range of 2 to 200.
15. The curable composition according to claim 13 or 14, characterized in that the ratio (W1 / W2) of the weight (W1) of the first inorganic hydroxide to the weight (W2) of the second inorganic hydroxide is within the range of 0.5 to 10.
16. The curable composition according to any one of claims 11 to 15, characterized in that the ratio of the filler component is in the range of 200 to 900 parts by weight per 100 parts by weight of the alkenyl group-containing polyorganosiloxane component.
17. The curable composition according to any one of claims 11 to 16, characterized in that the ratio of the filler component is in the range of 1,000 to 30,000 parts by weight per 100 parts by weight of the silicon-bonded hydrogen-containing polyorganosiloxane component.
18. 18. The curable composition according to any one of claims 11 to 17, characterized in that it does not contain a catalyst.
Citation Information
Patent Citations
Addition-curable silicone rubber adhesive composition and method for producing the same
JP2008156545A
Curable organopolysiloxane composition
JP2010144130A
Silicone rubber composition for high voltage electrical insulator and polymer insulator
JP2011231228A
Addition-curable silicone emulsion composition and release film
JP2013253176A
Thermoconductive silicone composition and thermoconductive silicone cured product
JP2020029524A